2008
DOI: 10.14254/2071-789x.2009/2-1/2
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Happiness – The Factors in Work Performance

Abstract: The paper analyses the role of work in human wellbeing, life satisfaction and happiness. The main problem is to relate the situation on Lithuanian labour market with individual wellbeing, life satisfaction and sense of happiness. Money does not buy happiness-this we know from many studies and from our personal experience. But what is the relationship between economics and happiness? This question is under many studies conducted by foreign psychologists and sociologists. The view that income does not have impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
1
14
0
2
Order By: Relevance
“…Interventions empowering healthcare professionals to enhance the synergy between their intrapersonal and interpersonal development are paramount for their happiness. From an individual standpoint, happiness is a result of being in harmony with one's life (Streimikiene and Grundey, 2009). Based on evidence in this review, individual determinants of healthcare professionals happiness do not operate mutually exclusively from the organizational determinants.…”
Section: Review Articlementioning
confidence: 93%
See 1 more Smart Citation
“…Interventions empowering healthcare professionals to enhance the synergy between their intrapersonal and interpersonal development are paramount for their happiness. From an individual standpoint, happiness is a result of being in harmony with one's life (Streimikiene and Grundey, 2009). Based on evidence in this review, individual determinants of healthcare professionals happiness do not operate mutually exclusively from the organizational determinants.…”
Section: Review Articlementioning
confidence: 93%
“…Among healthcare professionals in this review, time management, workload manageability, satisfaction with income, satisfaction with colleagues conduct and performance, having more sessions with clients, job rotation in the hospital wards and shifts were among the organizational dynamics that contributed to their happiness (Buaklee et al, 2017;Eckleberry-Hunt et al, 2016;Khosrojerdi et al, 2018). The more satisfaction one experiences both at work and in life, the happier they are likely to be and the better they are likely to perform (Argan et al, 2018;Streimikiene and Grundey, 2009). Therefore, policy makers should not only consider financial satisfaction but also enhance job satisfaction by improving organizational culture and dynamics.…”
Section: Review Articlementioning
confidence: 99%
“…Happiness plays a crucial role in success at work (Boehm & Lyubomirsky, 2008). A happy teacher is satisfied with what he or she do, and that is linked to the improvement of his or her productivity as a member of society (Streimikiene & Grundey, 2009). Happy early childhood teachers who are satisfied with their job can bring various sorts of Happiness to preschoolers and their parents (Lopez, 2008), and can exert a direct influence on preschoolers as well (Mäntylä, Uusiautti & Määttä, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Using OLS the authors found that a one percentage point increase in the unemployment rate lowers happiness levels by more than five times as much as one percentage point increase in the inflation rate. (Streimikiene & Grundey, 2009), this paper investigate the role of work in wellbeing, life satisfaction and happiness. This paper analyses the latest studies illustrate the impact of work on life satisfaction and happiness.…”
Section: The Relationship Between Happiness Inequality and Employmentmentioning
confidence: 99%